Bubble solutions for Hénon type equation with nearly critical exponent in RN. (December 2021) - Liu, Zhongyuan
Abstract: In this paper we study the Hénon type equation − Δ u + a ( x ) u = | x | α u p α − ε in R N, where p α = N + 2 + 2 α N − 2, α > 0, ε > 0, N ≥ 7 . We construct, for ε small enough, a family of positive solutions concentrating at the origin under certain conditions on the potential a ( x ) .